2008
DOI: 10.1097/01.jnr.0000387296.91677.61
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chinese Cultural Values on Taiwan Nursing Leadership Styles: Comparing the Self-Assessments of Staff Nurses and Head Nurses

Abstract: The purpose of this study was to investigate the influence of Chinese culture on nursing leadership behavior in Taiwan nurses. A descriptive study compared staff nurses' assessment of Chinese value in the leadership behavior of their head nurses. Data analysis was made on a convenience sample in Taiwan of 214 head nurses and 2,127 staff nurses who had worked with their head nurse for at least one year. Six medical centers and regional hospitals in northern (Taipei), central (Taichung) and southern (Kaohsiung) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
(13 reference statements)
1
13
1
Order By: Relevance
“…The directive leaders tended to be goal oriented, make quick decisions and assign work directly to each member, however, they might lack communication with staff members (Leadership with You ). This finding was similar to the finding of Chang () that under the influence of Chinese culture value, Taiwan head nurses emphasised the role of the director more than either that of a parent or mentor. Today, head nurses face more challenges from patients and their families, nurses, nursing departments and other disciplines.…”
Section: Quantitative and Qualitative Discussionsupporting
confidence: 88%
“…The directive leaders tended to be goal oriented, make quick decisions and assign work directly to each member, however, they might lack communication with staff members (Leadership with You ). This finding was similar to the finding of Chang () that under the influence of Chinese culture value, Taiwan head nurses emphasised the role of the director more than either that of a parent or mentor. Today, head nurses face more challenges from patients and their families, nurses, nursing departments and other disciplines.…”
Section: Quantitative and Qualitative Discussionsupporting
confidence: 88%
“…Among the traditional values and philosophies, Confucianism has the greatest impact on Chinese people, which appreciates the harmony with others and the respect for hierarchy. Therefore in China, to conflict with colleagues is inappropriate for educated people, and to challenge an authority or a superior role is even more inappropriate [47,48]. The reverence for authority role and superior and the obedience to situation deeply root in values, making nurses who are lower in the organizational hierarchies [49] perceive lack of authority to change practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Storr (2004) interviewed 18 leaders and managers in a district general hospital and suggested that effective leadership correlates with integrity and that the presence of integrity will improve organizational effectiveness. In Taiwan, both the staff nurses and head nurses scored themselves highest in personal integrity (Chang 2008). Because integrity is a key core value in nursing and a successful factor for leaders, nurse leaders should continue to integrate integrity into the management practice to ensure that effective nursing care is provided.…”
Section: Discussionmentioning
confidence: 99%